Food and Nutrition - Fieldhouse, Paul. author. aut Link
XIII, 253 p. 3 illus.
Keywords: As someone who was trained in the clinical sdentific tradition it took me several years to start to appreciate that food was more than a collection of nutrients, and that most people did not make their choices of what to eat on the biologically rational basis of nutritional composition. This realiza tion helped tobring me to an understanding of why people didn't always eat what (I believed) was good for them, and why the patients I had seen in hospital as often as not had failed to follow the dietary advice I had so confidently given. When I entered the field of health education I quickly discovered the farnaus World Health Organization definition of health as being a state of complete physical, mental and social well-being, and not merely the absence of disease. Health was a triangle -and I had been guilty of virtu ally ignoring two sides of that triangle. As I became involved in practical nutrition education initiatives the deficiencies of an approach based on giving information about nutrition and physical health became more and more apparent. The children whom I saw in schools knew exactly what to say when asked to describe a nutritious diet: they could recite the food guide and list rich sources of vitamins and minerals; but none of this intellectual knowledge was reflected in their own actual eating habits.